Considerations for clinical pharmacology studies for biologics in emerging markets. (March 2015) - Damle, Bharat; White, Robert; Wang, Huifen Faye; Korth‐Bradley, Joan; Mager, Donald; Meibohm, Bernd; Zhou, Hong Hui
Abstract Registration of innovative biologics in Emerging Markets (EMs) poses many opportunities and challenges. The BRIC‐MT countries (Brazil, Russia, India, China, Mexico, and Turkey) that are the fastest growing markets and regulators in these countries have imposed certain requirements, including the need for local clinical studies, for registration of biologics. The regulatory landscape in these countries is rapidly evolving, which necessitates an up‐to‐date understanding of such requirements. There is growing evidence which suggests that race, after accounting for body weight differences, may not influence the pharmacokinetics of biologics to the same extent that it does for small molecules. Thus, the requirements for clinical pharmacology trials in EMs are driven mainly by regulatory needs set forth by local Ministry of Health. In addition to the clinical Phase I to III studies done in the global program that supports registration in large geographies, countries such as China require local single and multiple dose Phase I studies. Participating in global studies with clinical sites within their country may be sufficient for some markets, while other regulators may be satisfied with a Certificate of Pharmaceutical Product. This paper discusses the current requirements for registration of innovative biologics in key EMs.